Development and implementation of a strategy for early diagnosis and management of scrub typhus: an emerging public health threat - Jain, Hitesh Kumar; Das, Arundhuti; Dixit, Sujata; Kaur, Harpreet; Pati, Sanghamitra; Ranjit, Manoranjan; Dutta, Ambarish; Bal, Madhusmita (Frontiers in Public Health, 2024)
Scrub typhus, caused by Orientia tsutsugamushi, is a re-emerging zoonotic disease in the tropics with considerable morbidity and mortality. The disease, mostly prevalent in rural areas, remains under-diagnosed, under-reported majority of the time because of low index of suspicion and nonspecific clinical presentation. Limited access to healthcare, diagnostics and treatment in rural settings further makes it challenging to distinguish it from other febrile illnesses. It is easily treatable but leads to severe form of the disease and death if not treated properly. As there is no existing public health program to address scrub typhus in India, there is an urgent need design a program and test its effectiveness for control and management of the disease. With this backdrop this implementation research protocol has been developed for a trial in few of the endemic "pockets" of Odisha, an eastern Indian state that can be scalable to other endemic areas of the country, if found effective. The main purpose of the proposed project is to include scrub typhus as a differential diagnosis of fever cases in every tier of public health system staring from community level to the health system for early diagnosis among those suspected and ensure complete treatment. The current article intents to describe the protocol of proposed Scrub Typhus Control Program (STCP) in details so that it can receive valuable views from peers which can further strengthen the attempt.